TRENDS OF CONTRACEPTIVE UTILISATION IN AMINU KANO TEACHING HOSPITAL, NORTHERN NIGERIA - Ibrahim AS; Takai IU; Rahila G (Ntec Specialist, 2015)
Background: The use of contraception in Northern Nigeria and indeed among clients in Aminu Kano Teaching Hospital (AKTH), Kano is in the increase. Objective: To determine the trend in contraceptive utilization among family planning clinic attendees in AKTH. Method: A retrospective review of the records of clients, who attended family planning clinic of AKTH over a 3 year period from 3rd January, 2011 to 31st December, 2013 was conducted. Results: A total of 8488 women attended the family planning clinic over the study period and up to 4679 clients accepted various forms of contraceptives. The contraceptive uptake was 55.1%. About half (49.8%) of the clients were between the ages of 20-29years and grandmultiparas constituted the largest (85.9%) group. Up to 31% of the clients were civil servants. There is a statistically significant (p =0.017) rising trend in the yearly utilization of contraception from 1033(12.17%) in 2011, 1284 (15.13%) in 2012, to 2362 (27.83%) in 2013. Injectable method was the most common accounting for 56.3%, while male condom was the least (0.17%). Vasectomy was however not recorded. Irregular vaginal bleeding was the commonest side effect (29.7%) experienced by the clients. Conclusion: There is a rising trend of contraceptive utilization in AKTH Kano. Male contraceptive utilization is however, extremely low. There is therefore the need to sensitized and enlightened men to avail themselves for contraception and this will encourage their spouses to improve on the use of the available methods